Heredity in comorbid bipolar disorder and obsessive-compulsive disorder patients - AMERIO, Andrea (Shanghai Arch Psychiatry, 2015)
Partly due to the overlap of symptom groupings in DSM, psychiatric comorbidity is extremely common. One of the most common and difficult to manage comorbid conditions is the co-occurrence of bipolar disorder (BD) and obsessive compulsive disorder (OCD). However, the key nosological question about this condition – whether they are two distinct disorders or a subtype of one of the disorders – remains unresolved. In order to help address this unanswered question, we updated our recent systematic review, searching the electronic databases MEDLINE, Embase, and PsycINFO to specifically investigate the heredity in BD-OCD patients. We identified a total of 8 relevant papers, the majority of which found that, compared to non-BD-OCD patients, BD-OCD patients were more likely to have a family history for mood disorders and less likely to have a family history for OCD. These results support the view that the majority of cases of comorbid BD-OCD are, in fact, BD cases. If confirmed in larger, more focused studies, this conclusion would have important nosological and clinical implications.